1994
DOI: 10.21000/jasmr94010138
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Acid-Base Accounting to Predict the Quality of Drainage at Surface Coal Mines in Pennsylvania, U.S.A

Abstract: Abstract:The effectiveness of Acid-Base Accounting (ABA) for predicting surface coal mine drainage quality in Pennsylvania was evaluated. Comparisons between ABA and mine drainage alkalinity, acidity, and sulfate were made for 38 mines in the bituminous coalfield. Neutralization Potential (NP), Maximum Potential Acidity (MPA), and Net Neutralization Potential (NNP) were evaluated with and without "thresholds."Calculations using "thresholds" counted only those values for NP greater than 30 mt CaC03/l,OOO mt and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 5 publications
1
20
1
Order By: Relevance
“…Studies analyzing ABA have used both methods. The results have been mixed (Brady and Cravotta, 1992; Brady et al, 1994). In general, the 31.25 factor for overburden MPA calculation is most commonly used.…”
Section: Summary Of Water Quality Prediction From Studies In West Virmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies analyzing ABA have used both methods. The results have been mixed (Brady and Cravotta, 1992; Brady et al, 1994). In general, the 31.25 factor for overburden MPA calculation is most commonly used.…”
Section: Summary Of Water Quality Prediction From Studies In West Virmentioning
confidence: 99%
“…Researchers at the Pennsylvania Department of Environmental Protection (PADEP) developed a method of volume adjustment with measurements of the areas to be mined (Brady et al, 1994). Due to the difficulty of measuring the surface area of each individual stratum, only the surface area of the upper and lower strata was measured.…”
Section: Summary Of Water Quality Prediction From Studies In West Virmentioning
confidence: 99%
“…Wood ash also significantly (P ≤ 0.001) decreased the soil exchangeable hydrogen in the Rubona Ultisol from the higher level of the control soils to the lowest levels below 0.25 cmolc kg −1 . Brady et al (1994), Charles et al (1999), Mokolobate and Haynes (2002), Naramabuye and Haynes (2006), and Fageria and Baligar (2005) have shown that the presence of calcium carbonate (CaCO 3 ) in the liming materials was responsible for the rise in the soil pH and decrease of soil exchangeable hydrogen, according to the equations CaCO 3 + H + → HCO 3 − + Ca 2+ ; HCO 3 − + H + → CO 2 + H 2 O (Fageria & Baligar 2005). The neutralization of H + then leads to the rise in soil pH.…”
Section: Resultsmentioning
confidence: 99%
“…The presence or absence of calcareous carbonate and silicate minerals in the rock sample/materials is extremely important in the AMD generation [12,13]. If the amount of these minerals in rocks is sufficient to offset the acid producing potential of the material, the acid drainage will not eventuate due to the neutralisation process, as long as the reaction rates of the respective materials are similar.…”
Section: Amd Generation and Its Controlmentioning
confidence: 99%